2019
DOI: 10.3390/antib8010006
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Immunoglobulin G to Protoporphyrin IX and Its Derivatives: Evidence the Fab Domain Recognizes the Protoporphyrin Ring

Abstract: Immunoglobulin G (IgG) is known to bind zinc via the Fc domain. In this study, biotinylated protoporphyrin IX (PPIX) was incubated with human IgG and then zinc-immobilized Sepharose beads (Zn-beads) were added to the mixture. After washing the beads, the binding of biotinylated PPIX with IgG trapped on Zn-beads was detected using alkaline phosphatase (ALP)-labeled avidin. Human IgG and its Fab domain coated on microtiter plate wells recognized biotin-labeled PPIX and its derivatives, Fe-PPIX and Zn-PPIX, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Thus, pioneering works with human and mouse myeloma-derived monoclonal Abs revealed unexpected high frequencies of molecules that interact with nitoarene compounds, especially 2,4-dinitrophenyl 1, 2, 3 . Further studies showed that the human Abs can also recognize other aromatic and heterocyclic molecules, including cofactors or prosthetic groups exploited by enzymes, namely - riboflavin, FAD, ATP, cobalamin, protoporphyrin IX and heme 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 . Human Abs also recognize a xenogenic disaccharide molecule i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, pioneering works with human and mouse myeloma-derived monoclonal Abs revealed unexpected high frequencies of molecules that interact with nitoarene compounds, especially 2,4-dinitrophenyl 1, 2, 3 . Further studies showed that the human Abs can also recognize other aromatic and heterocyclic molecules, including cofactors or prosthetic groups exploited by enzymes, namely - riboflavin, FAD, ATP, cobalamin, protoporphyrin IX and heme 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 . Human Abs also recognize a xenogenic disaccharide molecule i.e.…”
Section: Introductionmentioning
confidence: 99%